Screening of nutrients for improving flocculation performance of fungal bio-flocculants - Jebun, N.; Alam, Md. Zahangir; Mamun, Abdullah Al; Ahmad Raus, Raha (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
Flocculating agents are widely used in industrial processes, such as wastewater treatment, downstream process and food fermentation. Generally, synthetic organic polymer or inorganic coagulants (alum, ferric chloride, lime, etc.) are used for water and wastewater treatment. The use of these chemical coagulants is harmful to environment and health. On the contrary, the bio-flocculants are generally safe and environment friendly. Bio-flocculants are mainly composed of macromolecular substances, such as polysaccharides and proteins. The bio-flocculants production is affected by many factors such as nutrients of culture medium and nutrient concentration. In this study, screening tests were conducted aiming to find suitable nutrients and nutrients concentration of two potential strains (RWF-5 and RWF-6), which was measured in terms of reducing turbidity in Jar test. RWF-5 and RWF-6 showed good flocculating activity while malt extract was used as nutrient source compared to sucrose, yeast extract and starch. Supernatants of RWF-5 and RWF-6 cultured with malt extract were able to reduce turbidity from 900±10 NTU to 46 NTU and 195 NTU respectively. As such, bio-flocculants produced by these fungi have potential to be used in water and wastewater treatment industry.